ANALISIS PERSEPSI PENUMPANG TERHADAP KUALITAS PELAYANAN ANGKUTAN LAUT DI PELABUHAN REGIONAL SANANA KABUPATEN KEPULAUAN SULA PROVINSI MALUKU UTARA - Budiman Soamole; Parada Afkiki Eko Saputra (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
This research aims to know the quality of service ocean freight based on user perception. The service quality was explored is performance in Regional Port of Sanana and passenger ship KM. Intim Teratai, KM. Theodora, and KM. Bunda Maria.The instrument of service quality was adopted from 5 service quality dimention by Zeithaml, Parasuraman and Berry. Data collecting through spreading of queationnaire to service user and ship passenger in Regional Port of Sanana. The study successfully obtained 400 respondents (100 service user of port, 100 passenger of KM. Intim Teratai, 100 passenger of KM. Theodora, and 100 passenger of KM. Bunda Maria). The analysis was done by using Importance Performance Analysis (IPA) and calculating the Customer Satisfaction Index (CSI).Results were obtained with mean index value of port service user satisfaction from 8 service factor is 54,74 percent which satisfied the criteria entered. Complement facility in port terminal factor and information of ship schedule factor is entry to criteria less satisfied and get the prority for improved performance. Mean index value of ship passenger satisfaction KM Intim Teratai is 53,98 percent is entry to criteria sufficient satisfied, KM. Theodora is 55,10 percent is entry to criteria sufficient satisfied, and KM. Bunda Maria 67,10 percent which satisfied the criteria entered.